Characterization and Biofabrication of Silver Nanoparticles Utilizing Isochrysis Extract along with its in vitro Antibacterial and Antioxidant Applications - Gnanakani, S Princely Ebenezer; Amireddy, Krishnasurya; Dhanaraju, M D (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: At present, bio-green methods are more expedient than physical and chemical approaches due to their prompt, simple, lucrative, scalable and conservational synthesis of nanoparticles. Aim: This study investigates the extracellular biogenic synthesis of silver nanoparticles (AgNPs) using the ethanolic-hexane extract of Isochrysis sp. (EHEI). Materials and Methods: Biosynthesized AgNPs were nano-characterized by UV-Vis spectroscopy, Field Emission Scanning Electron Microscope (FESEM), Dynamic light scattering (DLS), X-ray diffraction (XRD), Energy Dispersive X-ray (EDX), Fourier Transform Infrared Spectra (FTIR), and Gas Chromatography Mass Spectrometry (GCMS) and finally examined for antibacterial and antioxidant activity. Results: The biosynthesis of AgNPs was evidenced with UV-Vis spectra showing surface plasmon resonance (SPR) at 421 nm; fabrication of highly stable, well dispersed, spherical AgNPs with an average size of 64.47 nm which were evidenced by FESEM. The crystalline nature of AgNPs was apparent from the diffraction peaks of XRD. The Zeta potential value of-22.3 mV demonstrated the colloidal stability of AgNPs. FTIR spectra showed that functional groups existing in fatty acids, lipids, proteins, xanthophylls, polyphenols and amines are accountable for the formation and stabilization of AgNPs. GCMS confirmed that biomolecules like fatty acid ethyl esters (FAEE) are involved in capping, biochemical reduction of Ag+ ions and stabilization of AgNPs. Also, the synthesized NPs displayed high antimicrobial activity against pathogenic G+ve and G-ve bacteria. In vitro antioxidant properties were ascertained by 1,1-diphenyl-2-picryl-hydrazyl (DPPH), hydrogen peroxide and reducing power assays which established that AgNPs have an incomparable scavenging potential than the extracts. Conclusion: Use of such a microalgal system postulates an alternative template for biofabrication of multifunctional nanomaterials in extensive prototype that might be extensively applicable in biomedical sectors.
Keywords: Isochrysis; AgNPs; FESEM; GCMS; Antibacterial; Antioxidant